SEXUAL INEQUALITY AMONGST MUSLIM ARABS - Ata, A. W. (Journal of Dharma, 1988)
In order to understand the make up and status of the Muslim woman up to the present, it is absolutely necessary to trace and examine thefactors and causes of her inequality with the man since the emergence of Islam. Against this background, the understanding of any progress inthe position of woman becomes easier and more understandable. Identifying the relevant causes would ultimately facilitate remedying of thedisease and ensure an effective treatment.